AB Initio Calculations of Theoretical Tensile Strength in Metals and Intermetallics - M. Šob; L. G. Wang; M. Friák; V. Vitek (The Minerals, Metals and Materials Society, 2001)
"The paper gives an account of applications of quantum-mechanical (first-principles) electronic structure calculations to the problem of theoretical tensile strength in metals and intermetallics. First, we briefly describe the way of simulating the tensile test and the electronic structure calculational method. Our approach is then illustrated on calculations of theoretical tensile strength in W, NiAl and transition metal disilicides MoSi2 and WSi2 with C11b structure. In Wand NiAl, we consider uniaxial tension along [001] and [111] directions. Although tungsten is elastically nearly isotropic (C44 = C”), theoretical tensile strength exhibits a marked anisotropy (oth/001 = 29 GPa, o'th/111 = 40 GPa). Calculated results compare favorably with experimental value of 24.7±3.6 GPa obtained for tungsten whiskers grown along the [110] direction. Similarly, in NiAl, the 'hard' orientation [001] differs very significantly from the [ill] orientation (oth/001 = 46 GPa, oth/111 = 25 GPa). This anisotropy is explained in terms of higher-symmetry structures present or absent on the calculated deformation paths. In disilicides, the theoretical strength is calculated for [001] loading (oth/001 = 37 GPa and 38 GPa for MoSi2 and WSi2 , respectively). The role of relaxation of internal structure parameter is discussed and changes in bonding conditions during the tensile test are analyzed.IntroductionIn most engineering applications, the strength of materials is limited by the presence of internal defects. If there were no defects, then, for example, the tensile strength could be several orders of magnitude higher and its value would be comparable with that of shear modulus. Therefore, the strength of ideal (defect-free) crystal represents an upper limit of attainable stresses, which is called the ideal strength. While it may not be possible to achieve the ideal strength in practice, it is not possible to exceed it. However, the ideal strength is already approached in situations which are technologically relevant. These include the low-temperature deformation of inherently strong materials, such as diamond, Si, Ge and some of the transition-metal carbonitrides, deformation of whiskers, nanoindentation of materials with low defect densities, hardened thin films and coatings etc. The ideal strength sets the limits of elastic stability of a solid. Its knowledge is useful for estimation of the ideal work of fracture stresses needed for homogeneous nucleation of dislocations and for modelling of crack propagation."